PENERAPAN METODE MENGHAFAL DAN BANDONGAN DALAM PEMBELAJARAN KITAB NAHWUDI PONDOK PESANTREN TANJUNG PASIR AL-AWWABIEN JAMBI - Nasution, Nur Cahaya (DIRASATUL IBTIDAIYAH, 2024)
AbstractThis research discusses the application of memorization and bandongan methods in learning the book of nahwu at the Tanjung Pasir Al-Awwabien Jambi Islamic Boarding School. This research aims to find out the process of applying the method, knowing the supporting and inhibiting factors as well as the efforts made by the teacher towards inhibiting factors in implementing the memorization and bandongan methods in learning the book of nahwu at the Tanjung Pasir Al-Awwabien Jambi Islamic Boarding School. This research uses a qualitative descriptive research method, where the researcher is the key instrument. The subjects in this research were nahwu subject teachers, Islamic boarding school students, the Head of Madin Wustho and the Khuwaidim of the Tanjung Pasir Al-Awwabien Jambi Islamic Boarding School. Data collection in this research used observation, interviews and documentation. The data analysis process consists of reducing data, presenting data and concluding. The results of this research show that there are several applications of memorization and bandongan methods in learning the book of nahwu at the Tanjung Pasir Al-Awwabien Islamic Boarding School, Jambi. The process method of memorizing: a). Encoding, b). Storage and c). Retrieval. Meanwhile, the bandongan method uses the process: a). A kiai or ustadz creates good communication, b). Starting teaching, c). At a high level of learning, the application of the sorogan method, d). Students ask questions and e). Closing. There are supporting factors, namely competent teachers, surrounding conditions and adequate facilities, while inhibiting factors are language factors, material that is too much and difficult to understand, different abilities of students, time allocation and wrong thinking of students. The efforts or solutions made include linking it with Indonesian, dividing sub-chapters in several meetings, re-explaining material that has not been understood, not pushing limits on memorization, paying more attention to students, providing motivation, flexible time and more innovative teachers. Keywords: Memorization Method; Bandongan Method; Nahwu Book.